RANDOMLY AMPLIFIED POLYMORPHIC DNA (RAPD) FINGERPRINTING OF SIX INDONESIAN POPULATIONS OF GIANT FRESHWATER PRAWN, Macrobrachium rosenbergii - Imron Imron; Dadan Sunandar; Rini Susilowati; Rommy Suprapto; Ikhsan Khasani (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2009)
Indonesia is rich of giant fresh water prawn (GFP) germ plasms. Best utilization of these resources for the purpose of either aquaculture development or conservation of genetic resources requires some information on the structure and levels of their genetic diversity. This study was aimed to characterize those GFP genetic resources by applying RAPD genetic markers. Six Indonesian populations of GFP from Asahan, Barito, Ciasem, Ogan, GImacro and Papua were collected and analyzed for their genetic variation using five RAPD primers. The results showed the diversity within the populations, as revealed by the level of polymorphism, ranged from 29% to 76% while genetic divergence between populations as shown by genetic distance ranged from 0.04 to 0.50. In terms of genetic divergence, two genetically distinct groups of GFP, namely the Papua GFP in one group and the remaining five GFP populations in the other, were identified. The results also showed the presence of specific population markers that are useful for genetic identification of GFP populations. Implication of these finding with regard to breed development is discussed.